2006
DOI: 10.1682/jrrd.2004.07.0089
|View full text |Cite
|
Sign up to set email alerts
|

Development of a teletechnology protocol for in-home rehabilitation

Abstract: Abstract-Our ability to provide in-home rehabilitation is limited by distance and available personnel. We may be able to meet some rehabilitation needs with videoconferencing technology. This article describes the feasibility of teletechnology for delivering multifactorial, in-home rehabilitation interventions to community-dwelling adults recently prescribed a mobility aid. We used standard telephone lines to provide twoway video and audio interaction. The interventions included prescription of and/or training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 43 publications
2
56
0
3
Order By: Relevance
“…Data presented on 13 patients (mean age, 58.2 years) indicated that on average 13.1 mobility/self-care problems per patient were identified and an average of 12.5 recommendations per patient were made to address these problems. 94 In summary, the findings suggest that HQ-VTC for telerehabilitation is feasible for delivery of in-home rehabilitation care.…”
Section: Table 4 Summary Of Recommendationsmentioning
confidence: 82%
See 1 more Smart Citation
“…Data presented on 13 patients (mean age, 58.2 years) indicated that on average 13.1 mobility/self-care problems per patient were identified and an average of 12.5 recommendations per patient were made to address these problems. 94 In summary, the findings suggest that HQ-VTC for telerehabilitation is feasible for delivery of in-home rehabilitation care.…”
Section: Table 4 Summary Of Recommendationsmentioning
confidence: 82%
“…94 The intervention used regular telephone service to provide low-quality 2-way video and audio interaction between the occupational therapist and patient regarding prescription and/or training in functionally based exercises,…”
Section: Feasibility Of Telemedicine By Pts/occupational Therapists Imentioning
confidence: 99%
“…In the literature [3], the authors pointed out the superiority of the proposed system to the other types of telehealthcare systems [4]- [9]. That is to say, the proposed portable high-definition video transmission system based on mobile communication is unique in comparison with other similar systems [7]- [9].…”
Section: Application In An Isolated Islandmentioning
confidence: 99%
“…TR can be defined as the application of telecommunication, remote sensing and operation, and computing technologies to the delivery of medical rehabilitation services at a distance. A growing amount of literature exists on the use of technology for remote assessment and intervention in medicine [1] and rehabilitation [2][3][4][5][6]. Schmeler et al recently reported on the state of the science of clinical and vocational assistive technology TR applications, outlining the current research, opportunities, and challenges [7].…”
Section: Introductionmentioning
confidence: 99%